Impact Of Communication And Innovation Variables On Adoption Of Sustainable Agricultural Practices - Adewale J. Alonge; Robert A. Martin (Journal of Applied Communications, 1992)
Groundwater non-point source contamination with agricultural chemicals from conventional high-input agriculture has become one of the major environmental concerns of the 1990s.